Noradregenic depression of neuronal excitability in the entorhinal cortex activation of TREK-2 K+ channels - Zhaoyang Xiao (2018)
The entorhinal cortex is closely associated with the consolidation and recall of memories, Alzheimer disease, schizophrenia, and temporal lobe epilepsy. Norepinephrine is a neurotransmitter that plays a significant role in these physiological functions and neurological diseases. Whereas the entorhinal cortex receives profuse noradrenergic innervations from the locus coeruleus of the pons and expresses high densities of adrenergic receptors, the function of norepinephrine in the entorhinal cortex is still elusive. Accordingly, we examined the effects of norepinephrine on neuronal excitability in the entorhinal cortex and explored the underlying cellular and molecular mechanisms. Application of norepinephrine-generated hyperpolarization and decreased the excitability of the neurons in the superficial layers with no effects on neuronal excitability in the deep layers of the entorhinal cortex. Norepinephrine-induced hyperpolarization was mediated by α 2A adrenergic receptors and required the functions of Gαi proteins, adenylyl cyclase, and protein kinase A. Norepinephrine-mediated depression on neuronal excitability was mediated by activation of TREK-2, a type of two-pore domain K+ channel, and mutation of the protein kinase A phosphorylation site on TREK-2 channels annulled the effects of norepinephrine. Our results indicate a novel action mode in which norepinephrine depresses neuronal excitability in the entorhinal cortex by disinhibiting protein kinase A-mediated tonic inhibition of TREK-2 channels. © 2009 by The American Society for Biochemistry and Molecular Biology, Inc.